Effects of superficial X-ray irradiation therapy at different intervals on collagen secretion of keloid fibroblasts - Wenyue ZHENG; Ji MA; Haiying ZANG; Qinglan FENG; Weijia WANG; Ciren MI; Chengcheng DENG; Dingheng ZHU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To investigate the effect of superficial X-ray irradiation at different intervals on the expression of collagen in human keloid fibroblasts and extracellular matrix, and to confirm the optimal irradiation interval. Methods The excised keloid tissue was collected and cultured primary human keloid fibroblasts. The third passage cells were used to set up an experimental group and a control group. Intervals (1, 2, 3, 4, 5, 6, 7 days) with superficial X-rays. Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot were used to detect the relative expression changes of collagen type Ⅰ and Ⅲ in cells. ELISA was used to detect the changes of type Ⅰ collagen in the extracellular supernatant, and preliminarily verified the optimal irradiation time interval for superficial X-ray therapy of keloids. One-way ANOVA was used to compare superficial X-ray irradiation groups at different intervals with the control group. The proportion of collagen type Ⅰ and type Ⅲ collagen mRNA decrease in each group was tested by independent samples t test. Results Compared with the control group, the expression level of type Ⅰ collagen mRNA in keloid fibroblasts in experimental group after shallow X-ray treatment at different time intervals showed a low peak at an interval of 3 days (t=12.09, P<0.01). The expression level of type Ⅲ collagen mRNA in experimental group had statistical significance decrease compared with the control group (P<0.05). The ratio of type Ⅰ collagen to type Ⅲ collagen in fibroblasts decreased most significantly at an interval of 3 days (t=6.67, P<0.01). The expression level of type Ⅰ collagen in HKF cells of each experimental group was significantly different from that of the control group (except for the interval of 7 days) (P<0.01), and there was a low peak at the interval of 1 day (t=9.97, P<0.01); The level of type Ⅲ collagen in HKF cells in experimental group was significantly different from that in the control group (P<0.01). The ratio of type Ⅰ collagen to type Ⅲ collagen increased gradually in the first 3 days, but there was no significant difference between the 5-day interval (t=0.21, P>0.05) and the 7-day interval (t=0.66, P>0.05). The expression of type Ⅰ collagen in extracellular supernatant of all experimental groups decreased by ELISA (P<0.05). The expression of type Ⅰ and Ⅲ collagen in cells and type Ⅰ collagen in extracellular supernatant of irradiation group showed a rising trend of collagen secretion after 7 days. Conclusion Controlling the irradiation interval within 3 days can significantly reduce the expression of collagen, which is of great significance for the clinical formulation of radiotherapy.